2019
DOI: 10.1111/all.14086
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the sensitization to nonspecific lipid transfer proteins from pollen and food: New role of allergen Ole e 7

Abstract: Background Ole e 7 is a nonspecific lipid transfer protein (nsLTP) from olive pollen, one of the main allergenic pollens worldwide. This allergenic nsLTP is responsible for severe symptoms in regions with high olive pollen exposure, where many Ole e 7‐sensitized patients exhibit a co‐sensitization to the peach nsLTP, Pru p 3. However, there is no evidence of cross‐reactivity, which explains this observed co‐sensitization. Therefore, the purpose of this study was to explore the relationship between Ole e 7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…95 A recent study reported that common IgG and IgE epitopes were identified in Ole e 7 and Pru p 3, with inhibition studies suggesting that primary sensitization to Ole e 7 could lead to sensitization to Pru p 3. 96 There has been some suggestion that the greater the atmospheric burden of birch pollen, the lower the incidence of nsLTP sensitization, leading to a hypothesis that high levels of birch pollen protect against nsLTP allergy. 97 It is suggested one potential explanation could be lower reactivity of effector cells exposed to the nsLTPs, as described by Christensen et al, on the basis of interference by other IgE molecules bound to the high-affinity IgE receptors on effector cells.…”
Section: Sensitization To Pollen Nsltp Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…95 A recent study reported that common IgG and IgE epitopes were identified in Ole e 7 and Pru p 3, with inhibition studies suggesting that primary sensitization to Ole e 7 could lead to sensitization to Pru p 3. 96 There has been some suggestion that the greater the atmospheric burden of birch pollen, the lower the incidence of nsLTP sensitization, leading to a hypothesis that high levels of birch pollen protect against nsLTP allergy. 97 It is suggested one potential explanation could be lower reactivity of effector cells exposed to the nsLTPs, as described by Christensen et al, on the basis of interference by other IgE molecules bound to the high-affinity IgE receptors on effector cells.…”
Section: Sensitization To Pollen Nsltp Allergensmentioning
confidence: 99%
“…Although it has less than 20% amino acid sequence identity with Pru p 3, recognition of Ole e 7 is associated with reactions to plant‐derived food (mainly peach, walnut and peanut), and 80% of Ole e 7 reactors are sensitized to food nsLTPs versus only 30% of Ole e 1 reactors 95 . A recent study reported that common IgG and IgE epitopes were identified in Ole e 7 and Pru p 3, with inhibition studies suggesting that primary sensitization to Ole e 7 could lead to sensitization to Pru p 3 96 …”
Section: Sensitization To Pollen Nsltp Allergensmentioning
confidence: 99%
“…Although the association between severe food allergy and sensitization to Ole e 7 has been described (24), two Spanish studies were unable to detect any correlation between peach and olive tree pollen in LTP hypersensitive subjects (25) and between food allergy and Ole e 7 (18), respectively. Nonetheless, recently the possibility of olive tree pollen being the primary sensitizer to LTP in regions with high exposure was put forward once more from Spanish authors based on in-vitro inhibition assays (26). Although about 80% of Ole e 7 reactors score positive to at least one plant food LTP ( 27), the fact remains that most Pru p 3 hypersensitive patients do not show any IgE reactivity to olive tree pollen on in-vivo testing (11).…”
Section: Olive Tree (Olea Europaea)mentioning
confidence: 99%
“…IgE specific to Pla a 3 could identify the subgroup of plane tree pollen allergic patients predisposed to allergy to food LTP [110 ]. Recently, new insights into the possibility that the olive LTP, Ole e 7, could play a role as a primary sensitizer in regions with a high olive pollen exposure has been confirmed [111 ].…”
Section: Class 1 Food Allergymentioning
confidence: 99%